Reducing the influence of perfectionism and statistics anxiety on college student performance in statistics courses - Wu, Rongjun; Chen, Juan; Li, Qi; Zhou, Hongcang (Frontiers in Psychology, 2022)
The influence of perfectionism and statistics anxiety on academic performance in statistics courses was investigated using a multidimensional perfectionism scale and a statistics anxiety rating scale. For perfectionism, the factor of personal standards had a significant direct positive effect on academic performance, while the factor of parental expectations was significantly negatively correlated with academic performance. Other factors (concern over mistakes, organization, and doubts about actions) did not significantly influence academic performance. For statistics anxiety, the two factors (test and class anxiety and computation self-concept) significantly impaired academic performance. These results indicated a need for innovation in classroom instruction and the reform of statistics course content and presentation to reduce statistics anxiety and improve personal standards. There is also a need to ensure that students better internalize parental expectations and to revise instructional design techniques to enhance students’ independent learning ability.